Oral Colonization by Candida Species in Patients with Multiple Sclerosis - da Cunha, Eliana Tomomi Shimabukuro [UNESP]; Figueiredo-Godoi, Lívia Mara Alves [UNESP]; Santos, Diogo Haddad; Carneiro, Rafael Paterno Castello Dias; do Olival, Guilherme Sciascia; de Barros, Patrícia Pimentel [UNESP]; Narimatsu, Keila; Tilbery, Charles Peter; Junqueira, Juliana Campos [UNESP] (Springer Nature, 2020)
Introduction: Multiple sclerosis (MS) is a chronic inflammatory demyelinating autoimmune disease that affects the central nervous system. Since immune system plays a key role in this disease, patients with MS can present higher risk of infections. Purpose: This study aimed to investigate the prevalence of Candida spp. in the oral cavity of MS patients in relation to a control group Methods: In total, 100 individuals were selected: 55 diagnosed with MS and 45 healthy individuals (control group). Saliva samples were collected and seeded in culture media selecting for Candida. Following an incubation period of 48 h, colony-forming units (CFU mL−1) were counted and colonies were isolated for Candida species identification by multiplex PCR. The results were analysed by chi-squared and Mann–Whitney U statistical tests considering a significance level of 5%. Results: Candida spp. were confirmed in the oral cavity of 50.09% patients in the MS group and 35.55% individuals in the control group. In individuals positive for the growth of Candida spp., the median values of Candida colonies were 220 CFU mL−1 for the MS group and 120 CFU mL−1 for the control group. However, no statistically significant differences were observed between groups for both prevalence and CFU mL−1 count. Of the Candida species identified, 73.91% were C. albicans, 21.73% C. glabrata, 2.17% C. tropicalis, and 2.17% C. krusei. Conclusions: The colonization of Candida spp. in the oral cavity of individuals with multiple sclerosis was higher than in the control group; however these findings were not proven to be statistically significant.
Keywords: Autoimmune disease; Candida; Candida albicans; Demyelinating disease; Microbiota; Multiple sclerosis